Observation on the Age at First Calving in the Savannah Breeds of Cattle in Northern Nigeria - Sackey, Anthony K.B.; Sanni, Bamidele D.; Abdullahi, Shehu U.; Fadason, T.S. (1999)
A total of 35 herds of cattle from 2 inistitutional farms, and 6 privately-owned farms which were semi-intensively managed, and 17 nomadic Fulani herds were studied between January 1984 and December 1993 to evaluate the age of first calving (AFC) in the three major indigenous breeds of the Savannah zone of Northern Nigeria: the White-fulani (bunaji), Sokoto-Gudali (Bokoloji) and red Fulani (Rahaji). The AFC of heifers at first calving ranged from 30 to 42 months (mean, 37±0.57 months) with no breed differences. The AFC of heifers from Semi-intensively managed herds (institutional and privately-owned farms) was 30 to 40 months ( mean, 36±1.05 months) and that from nomadic herds was 33 to 42 months (mean, 37±1.31 months). The much lower AFC range observed in this studycompared to the highervalues (33 – 60 months) reported by pervious investigators is due to the increased awareness of livestock owners for the need to improve feed supplementation for livestock in particular during the dry season. The nomadic herdsmen ensure a ready supply of cereal bran, cotton seed (meal or cake) crop residues such as groundnut and bean hulls, corn stalks in addition to salt (mineral) licks during the harsh dry season. Institutional and private herds are provided with legumes and grass silages and hay in addition to cereal bran, cotton seed meal and salt licks during the dry season. Nomadic herdowners now realize the importance of supplementary feeding and maintenance of good herd health in the prevention of malnutrition and diseases. This results in a consistent improvement in growth and productivity as evidenced by the lower AFC values observed in this study.